Exploring the Attitudes of School Staff towards the Role of Autism Classes in Inclusive Education for Autistic Students: A Qualitative Study in Irish Primary Schools - Catherine Rice; Neil Kenny; Leanne Connolly (MDPI AG, 2023)
The use of the designated special class model for autistic pupils in mainstream schools within the Irish education system has dramatically increased in recent years, as has the scrutiny regarding its alignment with increased policy focus on inclusive education. This qualitative study used semi-structured interviews to explore the views of twelve staff members, four special class teachers, four mainstream class teachers, and four principals of primary schools with special classes regarding the role of the special class model in supporting educational inclusion for autistic pupils. Results showed that participants felt specialist provision was an important aspect of appropriate provision for autistic pupils in Irish mainstream primary schools. Findings highlight the need for a tailored, child-centred approach to inclusion, given the challenges of mainstream class environments, with participants advocating for the safe space and support system of the special class for autistic pupils. Participants also identified challenges to inclusion, such as a lack of specialist training or CPD for teachers regarding inclusive practices and the tensions surrounding the inclusion of autistic children in mainstream settings. Principals have a critical role in developing inclusive school environments and supporting the special class. However, there is a need for greater support, training, and resources to help principals effectively fulfil their responsibilities. This underscores the need for departmental consideration of specific training, criteria, and continuous professional development to ensure effective support and inclusion of autistic students within the mainstream school environment.